Neurodevelopmental Outcomes in Preterm Infants at 12 Months of Corrected Age - Amama Javed, Misbah Arshad, Hira Ahmed, Muhammad Aizad Tanveer, Abdul Raheem, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Preterm babies are also more susceptible to delayed neurodevelopment because their brain is not fully developed and they also experience related neonatal complications. Early testing at corrected age aids in detection of delays in development and enables prompt action. Place and Duration of Study: This study was done in the Department of paediatrics and neonatology of Mayo Hospital Lahore from October 2022 to April 2023. Objective: To determine neurodevelopmental outcomes in preterm babies at the age of 12 months of corrected age. Methodology: This was a cross-sectional study of 250 preterm babies which was descriptive. The calculation of sample size was done with the use of formula of WHO sample size calculator. Infants who were born before 37 completed gestation weeks and attended follow up at 12 months of age were included. The infants with any major congenital anomalies or chromosomal disorders or severe neurological malformations were excluded. Information on gestational age, birth weight, neonatal complications and developmental milestones were taken. At 12 months corrected age, neurodevelopmental assessment was carried out using standard developmental assessment in gross motor, fine motor, language, cognitive, and social domains. The results of the data analysis were the rates of normal and delayed neurodevelopmental outcomes. Results: Among 250 preterm babies, most of them had the developmental age when they were 12 months corrected age. However, a large proportion exhibited the evidence of developmental delay, and it was predominantly in the gross motor and language domains. Infants with low gestational age, low birth weight, prolonged stay in the NICU, sepsis, respiratory distress and mechanical ventilation had a higher likelihood of developing developmental delay. Conclusion: Even premature infants are at risk of experiencing infancy neurodevelopmental delay. The frequent follow up at the corrected age is paramount in the early identification, parental counselling and early referral to rehabilitation services. Keywords: Preterm infants, neurodevelopment, corrected age, developmental delay, gross motor delay, language delay, low birth weight, neonatal outcome.